Agricultural soils and microplastics: Are biosolids the problem? - Radford, Freya; Horton, Alice; Hudson, Malcolm; Shaw, Peter; Williams, Ian (Frontiers in Soil Science, 2023)
Biosolids are the solid by-product of the wastewater treatment system. They are regularly applied to agricultural land in the UK to fertilize and increase crop yields, but they have been shown to contain high concentrations of microplastics. Here we sampled a selection of agricultural soils in the Southeast of England which had received or never received biosolid treatment. Sites were sampled on two occasions in the summer and winter. Microplastic numbers were high in both the biosolid treated fields (874 MP/kg) and the untreated fields (664 MP/kg) and a wide variety of polymers were found across sites. However, there was a lack of significant difference between treated and untreated soils. This suggests the influence of other microplastic sources e.g. agricultural plastic and general littering, and external conditions e.g. farm management and rainfall. Microplastic concentrations were higher in the summer suggesting that erosion, runoff, and wind transport may be removing microplastics from these systems. The dynamic nature of the agricultural soils may result in them becoming a vector for microplastics into the wider environment. The high variability in results seen here highlights the complexity of microplastic concentrations in heterogeneous agricultural soils. This study suggests that biosolids, whilst are likely a contributor, are not the sole source of microplastics in agricultural soils. Further research is required to determine source and sink dynamics in these systems. Understanding the sources of microplastic contamination in soils is imperative for future mitigation strategies to be effective.